On New Types of ω-Fibered Fitting Classes of Finite Groups - Vedernikov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We construct an infinite set of new types of ω-fibered Fitting classes of finite groups that differ from ω-local classes. We also describe the structure of maximal inner ω-satellites for the main types and establish a relationship between ω-fibered and Ω-foliated Fitting classes.